Manufacturing technology impact on environmental factors and manufacturing performance - Risyawati Mohd Ismail; Razli Che Razak; Halim Mad Lazim (Trans Tech Publications, 2014)
The purpose of this study is to study the impact of manufacturing technology in facilitating lean manufacturers in achieving superior manufacturing performance while operating with by various challenges from external environment. The paper is based on a survey research done on lean manufacturers in Malaysia and their adoption of manufacturing technology to couple the implemented lean system in mitigating challenges. The challenges faced by lean manufacturing firms in many developing countries includes adopting the right technology, using it efficiently and continuously reviewing production technology in order to gain maximum output. Model from this empirical study is expected to contribute towards the enhancement of theory on contingency and its effect on performance. At theoretical level, the study results showed that of manufacturing technology mediate the relationship between environmental factors and performance of lean manufacturers.